2018
DOI: 10.1152/ajpheart.00304.2018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced shift in right ventricular contraction pattern: novel marker of athlete’s heart?

Abstract: RV mechanical adaptation to long term, intense exercise imply a functional shift: the relative contribution of longitudinal motion to global function is increased, while the radial shortening is significantly decreased in athletes. Moreover, this functional pattern correlates with aerobic exercise performance, representing a potential new resting marker of athlete's heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…Under physiological conditions, the longitudinal shortening was suggested to account for the majority of RV pump function [ 5 ]; however, the majority of recent studies suggest a similar importance of longitudinal and radial motions (Fig. 2 ) [ 6 , 7 ]. Larger studies are needed to characterize potential age-related and gender-related alterations.…”
Section: Functional Pattern Of Rv Myocardial Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, the longitudinal shortening was suggested to account for the majority of RV pump function [ 5 ]; however, the majority of recent studies suggest a similar importance of longitudinal and radial motions (Fig. 2 ) [ 6 , 7 ]. Larger studies are needed to characterize potential age-related and gender-related alterations.…”
Section: Functional Pattern Of Rv Myocardial Mechanicsmentioning
confidence: 99%
“…Although very few prospective follow-up studies were performed in the field, current data suggest that the volumetric adaptation of the RV to exercise is more pronounced than that of the LV and that the eccentric type of hypertrophy is expected at all levels of training [ 53 ]. Resting global RV function is often in the low-normal range and data suggests a relative decrease in radial shortening along with maintained or increased longitudinal function [ 7 , 54 ]. Following ultraendurance sport events, however, the RV dimensions may increase, and decreased ejection fractions and GLS can be seen [ 54 ].…”
Section: Athlete’s Heartmentioning
confidence: 99%
“…By decomposing the model's motion along the three orthogonal anatomically relevant axes, volume loss attributable to either longitudinal or radial wall motions could be separately quantified. Thus, longitudinal EF (LEF), radial EF (REF) and their ratios to global RVEF [LEF index (LEFi) = LEF/RVEF, and REF index (REFi) = REF/RVEF] could be expressed as a measure of the relative contribution of the given direction to global function.To assess longitudinal and circumferential myocardial deformation, we computed 3D RVGLS and RVGCS as described elsewhere 15. …”
mentioning
confidence: 99%
“…The magnitude of EROA and regurgitant volume were associated with RV geometrical remodelling (RVEDVi vs. EROA: β = 0.41, R 2 = 0.15, P = 0.034; RVEDVi vs. regurgitant volume: β = 0.57, R 2 = 0.31, P < 0.001). Pre-operatively measured CVP, mPAP, PAWP, PVR, and DPG were 13[10][11][12][13][14][15][16] mmHg, 28 [21-36] mmHg, 17 [14-23] mmHg, 2.5 [1.8-3.5] Wood units, and 3 [1-…”
mentioning
confidence: 99%
“…The most pronounced structural changes have been observed in elite, competitive athletes; typically, biatrial and biventricular enlargement and/or hypertrophy are observed. [1][2][3] Functional measurements often result in low-normal values at rest. 1,4 Despite the pronounced cardiac remodeling in athletes, it is still a matter of debate whether exercise capacity can be predicted by cardiac size or by resting functional measurements.…”
mentioning
confidence: 99%